"Prancing" Heart With Pericardial Injury. Issue 14 (7th April 2015) - Suzuki, Kodai; Okada, Hideshi; Fukuta, Tetsuya; Yoshida, Shozo; Yoshida, Takahiro; Ishida, Narihiro; Shimabukuro, Katsuya; Iwata, Hisashi; Ushikoshi, Hiroaki; Toyoda, Izumi; Takemura, Hirofumi; Ogura, Shinji
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.